2021
DOI: 10.1080/10410236.2021.1875558
|View full text |Cite
|
Sign up to set email alerts
|

When Are We Going to Hold Orthorexia to the Same Standard as Anorexia and Bulimia?” Exploring the Medicalization Process of Orthorexia Nervosa on Twitter

Abstract: This study contributes to understanding medicalization on social media, by using Conrad's concept of medicalization as a theoretical framework to explore the conversation about Orthorexia Nervosa (ON) on Twitter. The aim of this mixed-methods study was twofold: the quantitative component aimed to provide descriptive information on the type of tweets and users, as well as on the network structure of the ONrelated conversation on Twitter, while the qualitative component aimed to explore how the medicalization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…To date, the relationship between orthorexia and weight is yet to be established, with some research suggesting that a lack of weight loss focus is a key distinction between orthorexia and other eating disorders [ 1 , 4 , 7 ]. Yet, other research indicates that a desire to manipulate weight and shape, and a drive for thinness and body dissatisfaction are core components of orthorexia [ 10 , 24 , 25 , 34 , 70 ], a theory supported by the findings of this study. Given that orthorexia is defined as the pursuit of optimal health, weight manipulation may be a component of orthorexia, as weight is commonly used as a proxy marker for health in an orthorexic society [ 19 , 51 ].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…To date, the relationship between orthorexia and weight is yet to be established, with some research suggesting that a lack of weight loss focus is a key distinction between orthorexia and other eating disorders [ 1 , 4 , 7 ]. Yet, other research indicates that a desire to manipulate weight and shape, and a drive for thinness and body dissatisfaction are core components of orthorexia [ 10 , 24 , 25 , 34 , 70 ], a theory supported by the findings of this study. Given that orthorexia is defined as the pursuit of optimal health, weight manipulation may be a component of orthorexia, as weight is commonly used as a proxy marker for health in an orthorexic society [ 19 , 51 ].…”
Section: Discussionsupporting
confidence: 72%
“…Healthism places the pursuit of health (and prevention of ill health) at the top of the moral virtue ladder, encouraging individuals to pursue it at all costs. In turn, an orthorexic society is created whereby orthorexic behaviors are normalized (and often praised), resulting in the development of a “socially acceptable eating disorder” or pseudo recovery for people experiencing diagnosable eating disorders [ 10 , 54 58 ]. In a systematic literature review on the psychosocial risk factors of orthorexia, McComb and Mills [ 2 ] reported that a history of an eating disorder is the strongest predictor of developing orthorexia, with previous engagement in dieting and poor body image also strong explainers [ 25 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…dietitians, researchers), with a very small number of people suffering from the disorder actually joining the conversation. The ON-related conversation on Twitter has been proven to bring about the medicalization process of ON, and the network analysis has shown that actors engaging in the ONrelated conversation on Twitter appear isolated from each other, with no formation of peer-support communities [32].…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of Instagram posts tagged with #orthorexia suggest that this community is largely defined by positive conversation and support around recovery [ 48 ]. A more recent mixed-methods study of ON on Twitter emphasized the contested medicalization of this diagnosis in social media conversations, which often compared it to more established diagnoses like BN and AN [ 49 ]. In contrast, research on BED and social media has focused on the ways social media use may promote binge eating behaviors, and not on the online representation of BED culture itself [ 50 ].…”
Section: Introductionmentioning
confidence: 99%